Clinical Outcomes of Second‐Line Chemotherapy in Patients with Previously Treated Advanced Thymic Carcinoma: A Retrospective Analysis of 191 Patients from the NEJ023 Study. (26th November 2019) - Tateishi, Kazunari; Ko, Ryo; Shukuya, Takehito; Okuma, Yusuke; Watanabe, Satoshi; Kuyama, Shoichi; Murase, Kyoko; Tsukita, Yoko; Ashinuma, Hironori; Nakagawa, Taku; Uematsu, Kazutsugu; Nakao, Mika; et al.
Abstract: Background: Owing to the rarity of this tumor, there is limited information about second‐line chemotherapy for patients with previously treated advanced thymic carcinoma. Material and Methods: We performed a multi‐institutional, retrospective study named NEJ023 for patients with advanced thymic carcinoma. Patients without indications for curative treatment were treated with chemotherapy from 1995 to 2014 at 40 institutions in the North East Japan Study Group. Demographic and clinicopathologic characteristics, data on treatment methods, and outcomes of second‐line chemotherapy were obtained from medical records. Results: In total, 191 patients were enrolled in this study. Second‐line chemotherapy included platinum‐based doublets in 57.6% of patients, other multidrug chemotherapy (e.g., cisplatin, doxorubicin, vincristine, and cyclophosphamide) in 13.6%, and monotherapy in 28.8%. The median follow‐up time was 50.5 months, and the median overall survival (OS) from the start of second‐line chemotherapy was 22.4 (95% confidence interval, 17.5‐26.7) months. The average response rate (RR) was 20.0% overall; it was 21.6% for patients treated with platinum‐based doublet chemotherapy, 13.6% for those treated with other multidrug chemotherapy, and 19.6% for those treated with single agent chemotherapy. There was no significant difference in OS between platinum‐based doublet chemotherapy, other multidrug chemotherapy, and monotherapy (the median OS was 22.4, 25.7, and 21.4 months, respectively). Conclusion: The median OS was 22.4 months in patients with advanced thymic carcinoma treated with second‐line chemotherapy. There were no significant differences in RR and OS between monotherapy and multidrug chemotherapy in this study. Implications for Practice: Owing to the rarity of this tumor, there is limited information about second‐line chemotherapy for patients with previously treated advanced thymic carcinoma. This is the largest data for those patients treated with second‐line chemotherapy. This study suggests there is no significant difference in efficacy between monotherapy and multidrug chemotherapy for previously treated advanced thymic carcinoma. This result can support the adequacy to select monotherapy as treatment of those patients. Abstract : Thymic carcinoma is rare and highly progressive. This study aimed to evaluate the efficacy of second‐line chemotherapy for patients previously treated for advanced thymic carcinoma and to identify promising chemotherapeutic regimens for clinical practice and further investigation.